Knowledge and concern towards endometriosis among Lebanese women: a cross-sectional study - Zeinab Kazan; Fatima Mroueh; Zeinab Hazime; Safaa Joumaa; Kassem Hamze; Adnan Husseini; Samir Mansour; Abbas Hoballah; Rana El Haidari (BMC, 2024)
Abstract Background Endometriosis is a prevalent disease among women worldwide, including the Middle East. Insufficient knowledge about the disease causes delayed diagnosis which could result in major complications, particularly infertility. Thus, being aware of the symptom's aids in prompt diagnosis and treatment. Furthermore, no research has been done in Lebanon to assess the Lebanese women's knowledge about endometriosis. Aim To determine the understanding and concerns of Lebanese women about endometriosis which aids in identifying knowledge gaps and misconceptions so that they can be addressed. Methods A cross-sectional study was conducted between February and March 2024 among Lebanese females, who completed the authors' online questionnaire assessing knowledge and concern about endometriosis and its associated symptoms, Multivariable logistic regression analysis was used to explore the relationship between score of knowledge and different characteristics of patients. Results A survey of 725 Lebanese women (mean age 32.5 years, SD = 9.5) revealed low knowledge (25.9%) about endometriosis origin, symptoms, and treatment. Over 60% were unaware of endometriosis symptoms, while 9.9% mistakenly believed menstrual cramps indicated the disease. Younger age (< 35 years), higher education (Master's degree or above), professional occupation, lower pregnancy and live birth rates, and no history of abortion, endometriosis, pelvic inflammatory disease, uterine or ovarian conditions, and pelvic surgeries were significantly associated with greater knowledge of endometriosis. Conclusion Lebanese women's knowledge of endometriosis is limited. This highlights how crucial medical education and awareness initiatives are in addressing the issue in Lebanon. Greater awareness of endometriosis will encourage Lebanese women to seek medical advice and consultation, resulting in earlier detection and treatment.